2022
DOI: 10.23960/jat.v10i1.5301
|View full text |Cite
|
Sign up to set email alerts
|

KERAGAMAN EMPAT AKSESI BUNGA MATAHARI (Helianthus annuus L.) MENGGUNAKAN PENANDA MORFOLOGI

Abstract: Bunga matahari (Helianthus annuus L.) merupakan tanaman introduksi dari Amerika Utara bagian Timur yang memiliki banyak kegunaan dan manfaat. Bunga matahari paling banyak dimanfaatkan sebagai tanaman penghasil minyak dan tanaman hias. Tanaman ini memiliki keragaman genetik yang besar sehingga dapat dikoleksi sebagai sumber plasma nutfah untuk kegiatan pemuliaan tanaman. Tujuan penelitian ini adalah untuk mengetahui keragaman morfologi empat aksesi bunga matahari. Penelitian ini dilaksanakan di lahan percobaan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…This is a very good potential to develop C. x grandiflorum in the cut flower business. The public also demands H. annuus, C. chinensis and G. jamesonii as ornamental plants and cut flowers as flower bouquets and wedding decorations [29,30]. Research has shown that a combination of 25% sugar and acetic acid significantly affects the freshness of flowers G. jamensonii [31].…”
Section: Resultsmentioning
confidence: 99%
“…This is a very good potential to develop C. x grandiflorum in the cut flower business. The public also demands H. annuus, C. chinensis and G. jamesonii as ornamental plants and cut flowers as flower bouquets and wedding decorations [29,30]. Research has shown that a combination of 25% sugar and acetic acid significantly affects the freshness of flowers G. jamensonii [31].…”
Section: Resultsmentioning
confidence: 99%
“…Where the grayscale color only has a color intensity of 0 -255 for each pixel. The grayscale transformation technique used is the average, where the grayscale image is obtained from finding the average value of the total RGB value using equation (1). The results of the transformation from RGB images into grayscale images from several samples of sunflower images can be seen in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…The average grayscale technique is performed by finding the average value of the total RGB values. This technique can be calculated using equation (1).…”
Section: Rgb To Grayscale Image Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tanaman bunga matahari memiliki ciri khas yaitu selalu menghadap sinar matahari yang disebut fenomena heliotropisme. Peristiwa tersebut secara alamiah terjadi saat bunga matahari sedang tumbuh dan berkembang karena bunga matahari menyimpan auxin (hormon tanaman yang mengendalikan pertumbuhan (Wahyudi, Rahmasari & Sari 2020) Bunga matahari sering kali dijadikan sebuah objek karya karena keindahan bunganya baik saat mekar bahkan saat sudah layu. Seniman memvisualisasikan bunga matahari dengan karakter dan keunikannya sendiri.…”
Section: Tematikunclassified